Photoelectricity properties of BaTiO3/γ-Fe2O3 composite granular film. (2nd January 2016) - Zhao, W. X.; Li, Q. L.; Sun, B.; Shen, Z.; Liu, Y. H.; Chen, P.
Abstract : Ag/[BaTiO3 /γ-Fe2 O3 ]/Si heterojunctions were grown by high vacuum magnetron sputtering system and were annealed at temperature 100–300°C under the vacuum conditions. All samples exhibit the rectification behaviour in the dark and under light irradiation. The resistive switching effect is observed in Ag/[BaTiO3 /γ-Fe2 O3 ]/Si heterojunctions. The resistive switching effect under white light irradiation is more obvious than that in the dark. The photovoltage effect and photoconductivity effect of Ag/[BaTiO3 /γ-Fe2 O3 ]/Si heterojunctions are observed and become stronger with increasing annealed temperature.